Carotane sesquiterpenes from Ferula vesceritensis: in silico analysis as SARS-CoV-2 binding inhibitors. Issue 57 (18th September 2020) - Mohamed, Tarik A.; Elshamy, Abdelsamed I.; Ibrahim, Mahmoud A. A.; Zellagui, Ammar; Moustafa, Mahmoud F.; Abdelrahman, Alaa H. M.; Ohta, Shinji; Pare, Paul W.; Hegazy, Mohamed-Elamir F.
Abstract : Sesquiterpenes, 8α-anisate-dauc-4-ene-3, 9-dione (webiol anisate) (1 ) and 10α-acetoxy-6α-benzoate-jaeschkeanadiol (2 ) as well as several analogues (3–12 ) were root extracted from Ferula vesceritensis . Abstract : Two sesquiterpenes, 8α-anisate-dauc-4-ene-3, 9-dione (webiol anisate) (1 ) and 10α-acetoxy-6α-benzoate-jaeschkeanadiol (2 ) as well as, ten known analogues (3–10 ), and two sesquiterpene coumarins (11–12 ) were isolated from an organic root extract of Ferula vesceritensis (Fam. Apiaceae). Chemical structures were elucidated based on IR, 1D- and 2D-NMR and HRMS, spectroscopic analyses. With molecular overlap observed between two protease inhibitors that are being examined as anti-COVID-19 drugs, and sesquiterpenes isolated here, metabolite molecular docking calculations were made using the main protease (M pro ), which is required for viral multiplication as well as RNA-dependent RNA polymerase (RdRp). In silico binding-inhibition analysis predicted that select F. vesceritensis sesquiterpenes can bind to these enzymes required for viral replication. Structures of the isolated constituents were also consistent with the chemo-systematic grouping of F. vesceritensis secondary metabolites with other Ferula species.